Identification of a Chemical Inhibitor with a Novel Scaffold Targeting Decaprenylphosphoryl-β-D-Ribose Oxidase (DprE1) - Matsunaga, Tatsuki; Monobe, Kohei; Aoki, Shunsuke (Infectious Disorders - Drug Targets, 2023)
Background: Tuberculosis is the second leading cause of death from infectious diseases worldwide. Multidrug-resistant Mycobacterium tuberculosis is spreading throughout the world, creating a crisis. Hence, there is a need to develop anti-tuberculosis drugs with novel structures and versatile mechanisms of action. Objective: In this study, we identified antimicrobial compounds with a novel skeleton that inhibits mycobacterium decaprenylphosphoryl-β-D-ribose oxidase (DprE1). Methods: A multi-step, in silico, structure-based drug screening identified potential DprE1 inhibitors from a library of 154,118 compounds. We experimentally verified the growth inhibitory effects of the eight selected candidate compounds against Mycobacterium smegmatis. Molecular dynamics simulations were performed to understand the mechanism of molecular interactions between DprE1 and ompound 4. Results: Eight compounds were selected through in silico screening. Compound 4 showed strong growth inhibition against M. smegmatis. Molecular dynamics simulation (50 ns) predicted direct and stable binding of Compound 4 to the active site of DprE1. Conclusion: The structural analysis of the novel scaffold in Compound 4 can pave way for antituberculosis drug development and discovery.
Keywords: molecular dynamics